2022
DOI: 10.1001/jamanetworkopen.2022.32787
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Universal Germline Genetic Testing for Patients With Breast Cancer

Abstract: ImportanceNational Comprehensive Cancer Network guidelines currently recommend germline testing for high-risk genes in selected patients with breast cancer. The clinical utility of recommending testing all patients with breast cancer with multigene panels is currently under consideration.ObjectiveTo examine the implications of universal testing of patients with breast cancer with respect to clinical decision-making.Design, Setting, and ParticipantsPatients from a previously reported cohort were assessed as in-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…In fact, a study showed that testing all patients with breast cancer (versus guideline-based testing) doubles the number of patients identified as having an actionable germline genetic result, 3 consistent with a report suggesting that restrictive testing may deny data-informed clinical management to patients with breast cancer. 4 Even in other cancers with clear testing guidelines such as ovarian, pancreatic, and metastatic prostate cancers, there is significant testing underutilization, perhaps because of the complexity of guidelines between cancers. 5 There is ample evidence that broad-based reflex testing of germline (providing the patient agrees) is necessary for individuals with a cancer diagnosis.…”
mentioning
confidence: 99%
“…In fact, a study showed that testing all patients with breast cancer (versus guideline-based testing) doubles the number of patients identified as having an actionable germline genetic result, 3 consistent with a report suggesting that restrictive testing may deny data-informed clinical management to patients with breast cancer. 4 Even in other cancers with clear testing guidelines such as ovarian, pancreatic, and metastatic prostate cancers, there is significant testing underutilization, perhaps because of the complexity of guidelines between cancers. 5 There is ample evidence that broad-based reflex testing of germline (providing the patient agrees) is necessary for individuals with a cancer diagnosis.…”
mentioning
confidence: 99%
“…In other models, the test result is always delivered by the genetics team 9,10 . However, it has been reported that many people carrying pathogenic variants might be missed were selection for testing to rely solely on the threshold in the current guidelines 11,12 …”
mentioning
confidence: 99%
“…9,10 However, it has been reported that many people carrying pathogenic variants might be missed were selection for testing to rely solely on the threshold in the current guidelines. 11,12 Significantly reduced DNA sequencing costs and increased testing capacity raises the possibility of universal germline testing of women with newly diagnosed breast cancer. 11 However, more rapid delivery of results would be required to incorporate them into management.…”
mentioning
confidence: 99%
“…21 A large multistate trial of 952 breast cancer patients found that 68.3% of patients who met criteria and 57.5% of those who did not meet criteria who had PGVs had positively impacted health outcomes related to a change in clinical management. 22…”
Section: Population Testing Outside the Setting Of A Specific Phenoty...mentioning
confidence: 99%